Gambaran Sanitasi Lingkungan pada Santriwati Penderita Demam Tifoid di Pondok Modern Darussalam Gontor Putri 3 - Wilda Magfirah; Nadia Saptarina; Amal Fadholah (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2022)
Good environmental sanitation will bear a good aesthetic and healthy environment. If the sanitation level is low then people around the neighborhood will be susceptible to disease. Environmental sanitation includes clean water supplying, the density of flies, garbage disposal facilities and sewage facilities (latrines). The purpose of this study was to determine the environmental sanitation strikes in Darussalam Gontor For Girls 3 and determine the cause of typhoid fever in Gontor For Girls 3. This study uses observation method with a descriptive approach. This research was conducted in Gotor for Girls 3 with the number of respondents as many as 42 people. Retrieval of data from respondents was conducted in January 2020 until February 2020.The results of this study was sanitation in Gontor For girls Campus 3 entered in both categories with the acquisition value of percentage as much as 66%. The factors that cause typhoid fever maybe of garbage disposal facilities, the level of flies density, water supplying and sewerage facilities (latrines), and the percentage of value about 46%.